Leucine-rich repeat receptor-like gene screen reveals that Nicotiana RXEG1 regulates glycoside hydrolase 12 MAMP detection - Yan Wang (Nature Portfolio, 2018)
The role of most plant leucine-rich repeat (LRR) receptors in innate immunity is unknown. Here, the authors develop virus-based constructs to silence LRR receptor-like genes in the Nicotiana benthamiana genome and identify Response to XEG1 that specifically recognizes the glycoside hydrolase 12 protein XEG1.